Corporate Financial Stability: An Immutable Link between Going Concern and Earning Capacity of Firms - Enyi , Enyi, Patrick (Current Aspects in Business, Economics and Finance Vol. 6, 2022)
Globally, investors have become more concerned about corporate survival than immediate financial gains. Most financial analysts use traditional solvency metrics to gauge the fiscal health of prospective firms presently. However, these metrics are often bereft of the adequacy and precision expected of the information they generate. Specifically, going concern valuations and firms’ financial stability metrics are corporate finance indices which are not always in alignment with individualized industrial analytics. This study aims to improve on this by comparing the efficacy of the existing fiscal health indicators of firms with their perceived going concern indices generated using the new measurement technique introduced in this study. Ex-post facto research was used in the study, which included 91 companies listed on the Nigerian Stock Exchange and the National Stock Exchange of India. Data analysis method includes multivariate regression analysis, ANOVA and Pearson correlation. Results indicate that the going concern ratio (GCR) introduced in this study has significant relationships with firms’ earning capacity, corporate financial stability ratio, Altman’s Z-score and Enyi’s relative solvency ratio (RSR). Nevertheless, the current ratio (CR) returned no significant relationship with GCR, implying that the effectiveness of the current ratio in determining corporate solvency status is seriously impaired in the face of changing financing paradigm.